Heart rate changes (HR) and oxygen saturation in blood (AO2) dependency in relation to the static apnea duration (STA) - Ognjen Pedja Tutorov (Exercise and Quality of Life)
In static apnea discipline diver holds the breath in standstill condition. Divingreflex represents a reaction of the body to apnea dive with responses of effectors:bradycardia, peripheral vasoconstriction, splenic contractions. Physiological significanceof these body changes implies reduction of oxygen consumption. The main objective ofthis research is to examine characteristics of connection between heart rate changes (HR)and changes in oxygen saturation in blood (SaO2) during apnea. A group of 15 breathhold divers was examined. Tests were conducted during static apnea, heart rate (HR) wasmeasured as well as oxygen saturation in blood (SaO2). The changes in HR and SaO2during apnea demonstrated statistically significant correlation. Higher HR values in apneaindicate higher mental tonus during apnea which is followed by higher muscle tonus. Theconsequence is a greater consumption of O2 and lower values of SaO2min. There isstatistically significant correlation between intensity of diving reflex activation andoxygen conserving (less reduction of SaO2).